The Routledge handbook of properties - Fisher, A. R. J. ca. 20./21. Jahrhundert; Maurin, Anna-Sofia 1969- (Routledge, 2024)
"Philosophical questions regarding both the existence and nature of properties are ubiquitous in ordinary life, the sciences, and philosophical theorising. In philosophy, it is one of the oldest topics discussed in various intellectual traditions - East and West - reaching back to Plato and Aristotle. Today, in the analytic tradition, properties continue to be a core area of study and research. The Routledge Handbook of Properties is an outstanding reference source to this perennial topic and is the first major volume of its kind. It contains forty specially commissioned chapters written by an international team of expert contributors, and is divided into nine clear parts: Methodology and Metaontology Distinctions Realism About Universals Nominalism Trope Theory Properties in Causation, Time, and Modality Properties in Science Properties in Language and Mind Properties in the Normative Realm, the Social World, and Aesthetics. The Routledge Handbook of Properties is essential reading for anyone studying and researching metaphysics, metametaphysics, and ontology, and will also be of interest to those in closely related areas such as philosophy of science, philosophy of language, philosophy of mind, ethics, and aesthetics"--
Keywords: Ideengeschichte; Philosophie; Eigenschaft; Tropes (Philosophy); Tropes (Philosophie); Aufsatzsammlung